1960
DOI: 10.1113/expphysiol.1960.sp001449
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate‐effects of Acute Hypoxia on the Heart Rate, Arterial Pressure, Cardiac Output and Ventilation of the Unanæsthetized Rabbit

Abstract: The circulatory and respiratory changes occurring during the first 5 min. of hypoxia were studied in unanawsthetized rabbits. Mild degrees of hypoxia produced an increase in ventilation in the rabbit, without eliciting a detectable circulatory response. The early circulatory effects consisted of bradycardia, a rise in mean arterial pressure and a fall in cardiac output, indicating predominant systemic vasoconstriction. The magnitude of the bradyeardia and rise in arterial pressure were related to the fall in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…The initial cardiovascular changes observed in the unanaesthetized rabbit in response to systemic hypoxia (Korner & Edwards, 1960) resemble closely those of the artificially ventilated dog, and the fall in heart rate is related closely to blood oxygen tension, which is in itself determined by ventilation volume. Korner (1965) points out that the rabbit, because of its shallow breathing, is less able than other species to increase alveolar ventilation when exposed to low oxygen concentrations.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The initial cardiovascular changes observed in the unanaesthetized rabbit in response to systemic hypoxia (Korner & Edwards, 1960) resemble closely those of the artificially ventilated dog, and the fall in heart rate is related closely to blood oxygen tension, which is in itself determined by ventilation volume. Korner (1965) points out that the rabbit, because of its shallow breathing, is less able than other species to increase alveolar ventilation when exposed to low oxygen concentrations.…”
Section: Introductionmentioning
confidence: 67%
“…Both bilateral vagotomy and denervation of the carotid body chemoreceptors abolish the bradycardia in rabbits (Korner & Edwards, 1960). Recently Chalmers, Isbister, Korner & Mok (1965) have reported that the sympathetic nervous system is important during hypoxia in maintaining cardiac output close to normal values in these animals.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of the sympathetic nervous system on the chronotropic effects is more difficult to assess. This is because the bradycardia in the rabbit is largely vagally mediated (Korner & Edwards, 1960a), and is the result of simultaneous activation in these experiments of the arterial chemoreceptors by hypoxia (Bernthal, Green & Revzin, 1951;Daly & Scott, 1958;Downing, Remensnyder & Mitchell 1962; Korner, 1965a) and of the baroreceptors by the blood-pressure changes. These vagal effects would oppose the chronotropic effects of initial beta-adrenergic activity.…”
Section: Effects Of Ganglion Blockmentioning
confidence: 90%
“…These sympatho-adrenal effects probably constitute the primary reflex response to arterial chemoreceptor stimulation in the anaesthetized rabbit since they are virtually abolished by section of the carotid sinus and aortic nerves. They also constitute part of the primary arterial chemoreceptor response of the unanaesthetized rabbit, where, in addition to the sympatho-adrenal effects, efferent vagal activity also increases (Korner & Edwards, 1960;Korner, 1965a;Korner, Langsford et al 1968).…”
Section: Effects In Animals With Section Of the Carotid Sinus And Aormentioning
confidence: 99%